Soil Stabilisation Using Pond Ash And Alcofine (International Journal of Innovative Research in Engineering & Management, 2022)
Need for locally produced building  materials is developing in third-world nations as a result of  the increased demand for new roads and apartment units  brought on by a growing population.. Over the years, the  availability of conventional material has not been  sufficient to meet the demand of growing population. However, using conventional methods and procedures  would require significant financial outlays in order to  create a vast network of roadways. According to Road  Note 31 (TRRI, 1977), the values of UCS for both BSL and  WAS were insufficient to stabilise the commercial range  of the OPC. For base courses of pavers, the UCS value of  the BSH compaction, however, can be acceptable. The  OPC/ALCCOFINE mix provides a long-term benefit in  terms of strength increase, as seen by the 28-day curing  period UCS values that were attained. The values of UCS  significantly increased from their initial conditions.. The  28 days curing period UCS produced a peak value of  2616kN/m2 at 30% pond ash & 3% alccofine for BSH  compaction, showing that the soil treated With this  mixture, base school curriculum for paving can be utilised  (during BSH compaction).. The unsoaked CBR values of  5, 7 and 11% (for the natural soil) compacted with BSL,  WAS and BSH energy efforts, respectively, increased to  46, 77 and 83% at 30% pond ash & 3% alccofine. The 24  hours soaked CBR values recorded peak values of 42, 66  and 66% with BSL, WAS, BSH energies, respectively,  which showed about 10-15% decrease from the unsoaked  CBR values. The CBR values of 66% with BSH  compaction at 30% pond ash & 3% alccofine blend can be  used as sub base material because it meets the 29%  recommended values specified in the Nigerian General  Specification for Sub-Base (1997).resistance to loss in  strength (Ola, 1983) based on 4 days soaking. The 6% OPC  6% ALCCOFINE treatment of the soil can be used, at BSH  compaction, for sub-base material because the soil was  subjected to a harsher condition (of 7 days soaking) and  due to the time dependent gain in strength advantage of the  pozzolana Also the 42% recorded with BSL compaction at  30% pond ash & 3% alccofine treatment meets the 15%  recommended for subgrade material by the Nigerian
Keywords: Pond ash; Alcofine; Natural Soil; CBR